HUBUNGAN ANTARA KONSEP DIRI DENGAN PENYESUAIAN DIRI GELANDANGAN DAN PENGEMIS DI PSBK PANGUDI LUHUR BEKASI - Habibullah Habibullah (Sosio Konsepsia, 2010)
This study aims to describe the self-concept, self adjustment and the relationship between self concept and adjustment of homeless people and beggars (gelandangan  an pengemis/gepeng) on the Panti Sosial Bina Karya Pangudi Luhur. Therefore, this study used a quantitative approach that will be done by cross sectional. The samples in this study using simple random sampling method. The results showed that 1). 57% of "gepeng" have a good selfconcept and 43% had bad self-concept, 52% "gepeng" a bad self-conceptadjustment and 48% had a good adjustment. 2). Results of cross tabulation: 30.16% of "gepeng" who has a good selfconcept and self-adjustment well, as much as 12.70% have good self-concept but a bad adjustment, 22.22 % of gepeng has a bad self-concept but a good adjustment and 34, 92 % of" gepeng" have bad self-concept and bad self-adjustment. 3). Alternative hypothesis in this study accepted that there is a relationship between self concept and self-adjustment at Gepeng on tlze PSBK Pangudi Luhur with positive correlation. Strength of the relationship between self concept and self-adjustment is weak, and therefore, this study can generalize the relationship of self concept and selfadjustment "gepeng" but the concept selfconcept "gepeng" a bit of influence on self-adjustment. Based on these results, it can recommend: 1). For Social Worker, care and rehabilitation of "gepeng" need to be adjusted based on the concept of self-2). For PSBK PL Luhur, should develop the ability of social workers in order to identify characteristics of clients who will become his responsibility. 3). For further research needs to be considered to see other factors that may affect or have relationships with self-adjustment.